Effect of Photodynamic Therapy on Aggressive Periodontitis - A Systematic Review (International Journal of Scientific Research and Management (IJSRM), 2017)
To analyze the available scientific evidence on the effects of photodynamic therapy with scaling and root planning on aggressive periodontitis. A broad literature search was performed using both electronic database and hand search. The databases like MEDLINE, COCHRANECENTRAL, GOOGLE SCHOLARS, EBSCO and PROQUEST were used for online search. Hand search was performed in the institute library, articles that satisfied the inclusion criteria comparing effectiveness of photodynamic therapy on aggressive periodontitis were selected. Included studies were subjected to critical analysis following the Cochrane Collaboration tool for evaluating the risk of bias. The initial search resulted in 112 articles; our final review included 8 articles. Out of 8 studies 6 studies showed photodynamic therapy as an adjunct to scaling and root planning was effective than scaling and root planning. 1 study showed antibiotics with scaling and root planning was effective than photodynamic therapy.1 study did not show any significant changes after photodynamic therapy. With the constraints of limited available literature photodynamic therapy is effective with scaling and root planning for the management of aggressive periodontitis. But, the antibiotics with scaling and root planning show a greater impact on the clinical outcomes of aggressive periodontitis